Progressive Pedagogy and Student-Centred Learning in Higher Education in Nepal - GC, Prem Bahadur (Academia Journal of Humanities & Social Sciences, 2026)
The changes have taken place in higher education due to globalization, technological development, and shifting workforce demand. The traditional one-way lecturer-centered pedagogy is less adequate in preparing students to address the 21st-century requirements of critical thinking, teamwork, and lifelong learning. This paper aims to explore the potential and practice of progressive pedagogy in an under-resourced institution of higher education in Nepal using the Deweyan philosophy of experientialism. Higher education faces a critical challenge in overcoming the limitations of traditional lecturer-centred pedagogy. Qualitative approaches were used to interview five experienced teachers at Myagdi Multiple Campus, Beni Bazaar, Nepal, employing a thematic analysis to determine the significant pedagogical practices. Eight central themes were identified: transforming the nature of authority of the teacher into a facilitator, experiential learning through workshops, democratic management of the classroom, learning that corresponds with the real world, formative holistic assessment, adaptation to technology, relationship pedagogy, and transformation advocacy. This study showed that progressive pedagogy which is a viable pathway in transforming higher education in Nepal to prepare students for global competitiveness, has been practiced despite the size, resources, and cultural issues, reflecting how global educational theories and practices are being interpreted from a South Asian perspective.